CAUSES OF SCHOOL ABSENTEEISM: CONFLICT EXPERIENCES OF PUPILS OF THE CHILDREN SOCIALIZATION CENTRE - Ciuladiene, Grazina; Kairienė, Brigita; Grigaitienė, Vitalija (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2021)
Destructive conflicts between a pupil and a teacher are considered to be one of the main reasons for avoiding school. Inappropriately managed conflicts lead to negative attitudes toward teachers and a school, course fear of the school. As a result of avoiding comes decrease in academic achievements, deteriorating relationships, dropping out of school. Research conducted in Lithuania shows that conflicts are often resolved in violation of the students’ rights and regardless of their interests; the applied forcing and avoiding strategies lead to conflict escalation as both the number of its participants and its objects increases, the actions of the conflict resolution process become more stringent. Therefore, the aim of the study is to reveal the courses of conflicts due to absenteeism. Applied research method is interview; data analysis method is thematic content analysis. 4 students of Children Socialization Centre were interviewed to gain information on the causes of their school nonattendance. Research results show that 4 main types of reasons are to be identified such as learning difficulties; usage of alcohol and drug; rejection of help of specialists; influence of the authority of friends. The study emphasizes the importance of preventing the escalation of conflicts in schools, and provides insights into alternatives for their constructive management.